Research progress on the role of PKM2 in the immune response - Liu, Chunyan; Liu, Chenchen; Fu, Rong (Frontiers in Immunology, 2022)
Pyruvate kinase (PK) is a key enzyme that catalyses the dephosphorylation of phosphoenolpyruvate (PEP) into pyruvate, and is responsible for the production of ATP during glycolysis. As another important isozyme of PK, pyruvate kinase M2 (PKM2) exists in cells with high levels of nucleic acid synthesis, such as normal proliferating cells (e.g., lymphocytes and intestinal epithelial cells), embryonic cells, adult stem cells, and tumour cells. With further research, PKM2, as an important regulator of cellular pathophysiological activity, has attracted increasing attention in the process of autoimmune response and inflammatory. In this review, we examine the contribution of PKM2 to the human immune response. Further studies on the immune mechanisms of PKM2 are expected to provide more new ideas and drug targets for immunotherapy of inflammatory and autoimmune diseases, guiding drug development and disease treatment.